2023
DOI: 10.1002/fsn3.3222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clarification on physicochemical properties and nutrient retention of pressed and blended cashew apple juice

Abstract: The cashew apple is a nutritious pseudofruit of the cashew tree, after the nut. It is highly perishable and has an astringent taste, which hinder its utilization in the food sector. This study was designed to optimize clarification of cashew apple juice (CAJ) using gelatine, and assess the effect of clarification on physicochemical properties (titratable acidity, total soluble solids, and pH), nutrient retention, and sensory quality of pressed and blended CAJ. CAJ was treated with gelatine concentrations (0, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
1
1
Order By: Relevance
“…The decreasing in the TSS content of NCTPPJ, NCMPPJ, ECTPPJ, ECMPPJ, TCTPPJ, and TCMPPJ pomegranate juices continued until the third month of storage at 4 °C. In our study, the significant changes in the TSS of the traditional clarified pomegranate juice during storage were different from that reported by ALUKO et al (2023). The authors reported no significant changes after juice clarification, and these differences would be due to that different clarification conditions.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The decreasing in the TSS content of NCTPPJ, NCMPPJ, ECTPPJ, ECMPPJ, TCTPPJ, and TCMPPJ pomegranate juices continued until the third month of storage at 4 °C. In our study, the significant changes in the TSS of the traditional clarified pomegranate juice during storage were different from that reported by ALUKO et al (2023). The authors reported no significant changes after juice clarification, and these differences would be due to that different clarification conditions.…”
Section: Resultscontrasting
confidence: 99%
“…In general, the obtained findings agree with DERELI et al (2015), DAVARCI et al (2019), WANG et al (2022) and ALUKO et al (2023.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation